2019
DOI: 10.1093/ndt/gfz087
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and characteristics of acute kidney injury in the Southeast Asia intensive care unit: a prospective multicentre study

Abstract: Background Etiologies for acute kidney injury (AKI) vary by geographic region and socioeconomic status. While considerable information is now available on AKI in the Americas, Europe and China, large comprehensive epidemiologic studies of AKI from Southeast Asia (SEA) are still lacking. The aim of this study was to investigate the rates and characteristics of AKI among intensive care unit (ICU) patients in Thailand. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 38 publications
7
48
0
1
Order By: Relevance
“…A recent study conducted by Srisawat, et al reported that the incidence of AKI stage 3 among patients in ICU was 28.9%; 16.4% of the patients at ICU had AKI stage 2 and 7.5% had AKI stage 1. 11 Aside from that, they also showed that when the patients were admitted to ICU, most of the AKI patients progressed to AKI stage 3. This can be explained that AKI was not recognized in time so was not treated appropriately by the time the patients were admitted to the ICU.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study conducted by Srisawat, et al reported that the incidence of AKI stage 3 among patients in ICU was 28.9%; 16.4% of the patients at ICU had AKI stage 2 and 7.5% had AKI stage 1. 11 Aside from that, they also showed that when the patients were admitted to ICU, most of the AKI patients progressed to AKI stage 3. This can be explained that AKI was not recognized in time so was not treated appropriately by the time the patients were admitted to the ICU.…”
Section: Discussionmentioning
confidence: 94%
“…Informed consent was waived. This study is part of the Southeast Asia-Acute Kidney Injury (SEA-AKI) study that has been previously described by Srisawat et al 6 Demographic and clinical data from all of the participants were collected such as admission date, sex, age, body mass index (BMI), primary diagnosis at ICU admission, history of comorbid conditions, AKI stages, RRT modes, and the use of mechanical ventilation during ICU stay. The severity of participants was determined by the Acute Physiology and Chronic Health Evaluation II (APACHE II) and Sequential Organ Failure Assessment (SOFA) scoring system.…”
mentioning
confidence: 99%
“…We also found that predictive ability of SEA-MAKE score was higher in university and regional hospitals than provincial hospitals (Additional file 1: Table S4). Formal sample size calculation was not calculated in our study because it was fixed to the Southeast Asia AKI study [10]. All available data of the cohort were used to maximize the power and generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Only data from the first admission were used if the patients have been admitted to the hospital several times during the study period. Formal sample size was not calculated because it was fixed to the Southeast Asia AKI cohort [10]. All available data were used to maximize the power and generalizability of the proposed model.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…According to research, the Rate of AKI in community hospitals is about 2%, while in large academic institutions, the rate of AKI accounts for more than 20% of all hospitalisations [9,10]. In addition, if specific hospital units are studied such as ICU, cardiac surgery,and transplant centers, the rate of AKI can be 50% or more [11,12] .…”
Section: Introductionmentioning
confidence: 99%